2022
DOI: 10.7150/jca.59286
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Metastasis-Related Protein IFI16 in Esophageal Cancer using a Proteomic Approach

Abstract: Background: Metastasis is the leading cause of the high morality of esophageal squamous cell carcinoma (ESCC), so early monitoring metastasis of esophageal cancer is the key to improve the survival rate of ESCC patients. However, there have not been effective biomarkers for predicting metastasis of ESCC patients,it is an urgent need to identify ESCC metastasis-related proteins. Methods: iTRAQ-based proteomic method was performed in highly metastatic 30M cell established in our previous study and the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In this study, our cDNA microarray analysis revealed that IFI16 expression is upregulated in ESCC cell lines when co-cultured with macrophages. This finding aligns with research by Wang et al, who identified high IFI16 expression in highly metastatic ESCC cells using a proteomics approach [26]. They characterized IFI16 as a protein associated with metastasis in ESCC and observed that silencing IFI16 led to decreased levels of fibroblast growth factor proteins FGF1 and FGF2 in 30M cells, a derivative of the KYSE30 cell line and a model for ESCC metastasis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, our cDNA microarray analysis revealed that IFI16 expression is upregulated in ESCC cell lines when co-cultured with macrophages. This finding aligns with research by Wang et al, who identified high IFI16 expression in highly metastatic ESCC cells using a proteomics approach [26]. They characterized IFI16 as a protein associated with metastasis in ESCC and observed that silencing IFI16 led to decreased levels of fibroblast growth factor proteins FGF1 and FGF2 in 30M cells, a derivative of the KYSE30 cell line and a model for ESCC metastasis.…”
Section: Discussionsupporting
confidence: 89%
“…Following the report of FGF proteins [26], since cytokines whose expression were regulated by IFI16 may be involved in the malignant phenotype of ESCC, we also searched comprehensively for cytokines whose expression is downregulated by IFI16 knockdown using a cytokine array. This cytokine array also included FGF2 (alternative name FGF basic, C9 and C10 spots in Supplementary Figure S1), but we could not detect any FGF2 spots in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative proteomics has been widely used in oncology to identify biomarkers with diagnostic and therapeutic potential (Wang et al, 2018;Wang et al, 2022). Isobaric tags for relative and absolute quantitation (iTRAQ), a new protein quantitation technique, has the advantages of a simpler labeling process, higher sensitivity, and a wider application range compared with traditional quantitative methods.…”
Section: Introductionmentioning
confidence: 99%